Tratamiento jurídico de violencia intrafamiliar normas, protocolos y manejo en ecuador - Jaramillo Pardo, Bella Veronica (Machala : Universidad Técnica de Machala, 2019)
Introduction: Domestic violence is a social problem that has suffered Ecuador and the world for decades, the same that does not respect age, sex, or social position, where it is estimated that 9 out of 10 people report some type of aggression or violence in the family. Objective; General: Describe intrafamily violence, through the analysis of the norms, protocols and status of Ecuador, for the legal treatment in cases that are reported. Specific: Identify the rules that are regulated, know existing protocols and interpret the Positive Law in relation to intrafamily violence in the Ecuadorian state. Method: The methodology applied in this project is the revision of scientific articles, in the pages such as: Scielo, DIALNET, MEDLINE, Constitution of the Republic of Ecuador, Norms and Protocols for Intrafamily Violence, Organic Law, among others. They have identified about 18 scientific articles that narrate the proposed theme, including laws, rules and regulations as statutes of the Ecuadorian State, these are inserted into the Mendeley platform, which manages to cite them with Vancouver standards. Conclusion: It was concluded that there are norms, protocols, regulations and statutes that govern the Ecuadorian state regarding intrafamily violence, due to the increase in the rate of violent deaths (femicide, or homicide), the same ones that are being executed in all fields: health, housing, education and employment.
Introducción: La violencia intrafamiliar es un problema social que ha sufrido el Ecuador y el mundo desde hace décadas atrás la misma que no respeta edad, sexo, o posición social, en donde se estima que 9 de cada 10 personas denuncian algún tipo de agresión o violencia en la familia. Objetivo; General: Describir la violencia intrafamiliar, mediante el análisis de las normas, protocolos y Estatus del Ecuador, para el Tratamiento Jurídico en los casos que se reportan. Específicos: Identificar las normas que se regulan, conocer protocolos existentes e interpretar el Derecho Positivo en relación a la violencia intrafamiliar en el estado ecuatoriano. Método: La metodología aplicada en este proyecto es la revisión de artículos científicos, en las páginas tales como: Scielo, DIALNET, MEDLINE, Constitución de la Republica de Ecuador, Normas y Protocolos para Violencia Intrafamiliar, Ley Orgánica, entre otros. Se han identificado cerca de 18 artículos científicos que narran la temática propuesta, entre leyes, normas y reglamentos como estatutos del Estado Ecuatoriano, estos son insertados dentro de la plataforma Mendeley, la misma que logra citarlos con las normas Vancouver. Conclusión: Se concluyó que si existen normas, protocolos, reglamentos y estatutos, que rigen al Estado Ecuatoriano en cuanto a violencia intrafamiliar, debido todo esto al incremento en la tasa por muertes violentas (femicidio, u homicidio), las mismas que están siendo ejecutadas en todos los campos: salud, vivienda, educación y laboral.
Keywords: VIOLENCIA INTRAFAMILIAR; ECUADOR,; NORMAS; PROTOCOLOS